АSSESSMENT AND FORECASTING OF FLIGHT SAFETY LEVEL OF AIRLINE - E. S. Prozorov (Научный вестник МГТУ ГА, 2016)
The article presents methods based on probability theory and mathematical statistics for solving a number of basic problems: formation and evaluation of the current flight safety level; forecasting the level of flight safety; ranking the objects (planes, pilots) in terms of flight safety; evaluation of the presence (or absence) of control actions arising in the context of the organization of corporate safety management system. At the same time as the main source of information are considered forward-looking events received from flight data.